Efektivitas E-Learning terhadap Kemampuan Koneksi Matematis Siswa di Kelompok Kerja Madrasah Tsanawiyah Kabupaten Tulungagung - Elly Susanti; Turmudi Turmudi; Muhammad Nafie Jauhari; Sri Harini; Ahmad Lubab; Anisatur Rizqiyah (Jurnal Tadris Matematika, 2020)
Madrasah students' mathematical connection skills need to be of particular concern in the process of learning mathematics. Connection skills are the base for students to connect concepts in mathematics, mathematical concepts with other science concepts and mathematical concepts with everyday life. One of the efforts made in overcoming this problem is to use e-learning. Descriptive quantitative research methods are used to see how effective e-learning is for students' mathematical connection abilities. A total of 30 students were selected as research samples for data collection. Data processing techniques were divided into control groups and subsequent experiments were analyzed using descriptive statistics. The results showed that the effectiveness of technology-based e-learning included moderate criteria with an ING score of 0.56, whereas the study group without e-learning included moderate criteria with an ING value of 0.29. In conclusion, there is an increase in student learning outcomes after using e-learning media. t-test was obtained > with 0.007 <∝ (0.05) indicating that e-learning was effective to improve the mathematical connection ability of Madrasah Tsanawiyah students.